2020
DOI: 10.1007/s42844-020-00012-8
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Parenting Is Indirectly Linked to Delayed Reward Discounting via Blunted RSA Reactivity: the Protective Role of a Shift-and-Persist Coping Strategy

Abstract: Exposure to adverse parenting experiences, either from being reared under conditions of threat or deprivation, is a major source of chronic stress that is linked to youths' dysregulated stress responses and impulsive decision-making. Many youth, however, adapt well and develop optimal decision-making despite the experience of adversity. Research has shown that the use of cognitive strategies to cope with stress, such as accepting and adapting to an acute stressor (i.e., shifting) and effortfully pursuing futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 103 publications
(142 reference statements)
2
10
0
Order By: Relevance
“…5 Kawasaki University of Medical Welfare, Kurashiki, Japan. 6 Department of Psychology, Graduate School of Humanities and Social Sciences, Hiroshima University, Higashi-Hiroshima, Japan.…”
Section: Author Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Kawasaki University of Medical Welfare, Kurashiki, Japan. 6 Department of Psychology, Graduate School of Humanities and Social Sciences, Hiroshima University, Higashi-Hiroshima, Japan.…”
Section: Author Contributionsmentioning
confidence: 99%
“…Hence, we focused on the shift-and-persist strategy (S-P; [ 5 , 6 ]), which is considered an effective coping strategy for protecting psychological health and reducing risky and impulsive decision-making of low SES individuals. Furthermore, we addressed a moderated mediation model in which SES led to career choice anxiety and influenced career exploration, as in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some studies have found blunted cardiovascular responding to be predictive of cardiac events and even death in the long term (Eguchi et al., 2009; Phillips, 2011). Similarly, chronically stressed individuals who show reduced persistence may be displaying an effective short‐term strategy to preserve energy—though reduced persistence may carry long‐term consequences for academic, vocational, and social domains (Del Giudice et al., 2011; Liu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Human studies suggest that blunted heart rate or bradycardia can be indicative of a freeze-type response (Lojowska et al, 2018;Löw et al, 2015;Roelofs, 2017). Similarly, human studies have found that the freeze response is associated with attenuated RSA withdrawal (i.e., keeping on the parasympathetic "brake" in the face of a stressor) (Buss et al, 2018;Liu et al, 2020). Blunted heart rate acceleration and attenuated or absent RSA withdrawal under stress suggests a lack of mobilization (and potentially a degree of burnout) in the body's "fight-or-flight" responses (Brotman et al, 2007;McLaughlin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation